Gender Determination from Toe Prints Among Kagay-Anons of Philippines for Forensic Application - Nataraja Moorthy T; DevinaKD; Ariel Philip IP (Indian Journal of Forensic Medicine & Toxicology, 2021)
Footprint is a physical evidence, often found at the crime scenes. Due to its ability to provide moreinformation than fingerprint, it has been considered as a valuable clue. Sometimes, partial footprints or toeprints are found in crime scenes. Hence the present study used toe prints among Kagay-Anons of Philippinespopulation for gender determination. A total of 4000 toe prints were collected and analyzed by “Acreemethod”, using 5mm x 5mm square area transparent film. The number of ridges within the square wascalculated as ridge density. The finding has shown that females havecomparatively higher ridge density thanmalesin all five toes. The present study shows that partial foot print found at the crime scene can be stillcollected and analyzed for identification